1997
DOI: 10.1002/(sici)1097-0142(19970315)79:6<1195::aid-cncr19>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive epidemiology of cerebral gliomas in France

Abstract: histologic confirmation (M/F ratio of 2.6; P Å 0.008). Between 1983 and 1990, an increasing trend of 5% per year was observed in the incidence of malignant astrocytomas in the population older than 65 years.CONCLUSIONS. These data confirm the observation made in other countries that the incidence of primary brain tumors (particularly malignant astrocytomas) is increasing in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0
3

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(55 citation statements)
references
References 27 publications
4
48
0
3
Order By: Relevance
“…Because data in that population are calculated from the time of diagnosis, OS and PFS were calculated from the time of surgery and the time of study inclusion. PFS and OS were then stratified by age (Ͼ 75 years or Ͻ 75 years), KPS at study entry (postsurgery; Ͼ 60 or Ͻ 60), median tumor size (Ͼ 15.75 cm 2 or Ͻ 15.75 cm 2 ), and type of response (CR, PR, or SD). Survival curves were compared using the log-rank test at an ␣ level of 0.05.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because data in that population are calculated from the time of diagnosis, OS and PFS were calculated from the time of surgery and the time of study inclusion. PFS and OS were then stratified by age (Ͼ 75 years or Ͻ 75 years), KPS at study entry (postsurgery; Ͼ 60 or Ͻ 60), median tumor size (Ͼ 15.75 cm 2 or Ͻ 15.75 cm 2 ), and type of response (CR, PR, or SD). Survival curves were compared using the log-rank test at an ␣ level of 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] For example, some investigators have reported an increase of 5% per year in the portion of population age Ն 65 years. 2 Another study showed that, although it remained relatively stable in the younger segment of the population, the incidence of GBM increased by Ͼ 20% in patients ages 70 -74 years between 1980 and 1990.…”
mentioning
confidence: 99%
“…For example, the ageadjusted annual incidence rate of glioma in the United States is 7.6 in 100,000 in males and 5.4 in 100,000 in females (2), and the male-to-female excess has been stable over time and is evident internationally (7)(8)(9). Using New York State tumor registry data for the period from 1976 to 1995, McKinley et al (7) calculated crude, and age-and sex-specific incidence rates for three types of glial tumors: glioblastoma multiforme, astrocytoma not otherwise specified, and anaplastic astrocytoma.…”
Section: Descriptive Epidemiologymentioning
confidence: 99%
“…The annual incidence rates of primary brain tumours in the United Kingdom, France, Norway and Finland and mortalities per 100 000 population are similar to those in the United States (Muir et al, 1994;Fleury et al, 1997;Prados and Levin, 2000). The incidence of brain cancer may be increasing in older people (Muir et al, 1994).…”
mentioning
confidence: 65%